Barbie as Rapunzel - Ruby, Cliff; Lesser, Elana; Durchin, Jesyca C.; Twiner-McCarron, Jennifer; Hurley, Owen.; Huston, Anjelica; Summer, Cree.; Roth, Arnie; Mattel Entertainment (Firm); Mainframe Entertainment (Firm); London Symphony Orchestra; Universal Studios Home Entertainment (Firm) (Universal City, CA : Universal Studios Home Entertainment, 2010)
Rapunzel had the most beautiful, radiant hair the world had ever seen. But Rapunzel's life was far from wonderful. She lived as a servant of Gothel, a jealous, scheming witch who kept her hidden deep in a forbidding forest, guarded by the enormous dragon Hugo and surrounded by an enchanted glass wall. Rapunzel's discovery of a magic paintbrush leads her on a journey that will unravel a web of deception, and bring peace to two feuding kingdoms.
Title from container.
Originally produced as a motion picture in 2002.
Release date: Nov. 16, 2010.
Note: Container has misspelled Jennifer Twiner McCarron's name as Jennifer Twiner McCarrona and Arnie Roth's name as Arnie Rot.
Special features: Rapunzel's art gallery ; dress-up Rapunzel game ; The artist in me documentary.
Music by Arnie Roth, music performed by London Symphony Orchestra.
Keywords: Barbie (Fictitious character) -- Juvenile films; Fairy tales -- Adaptations -- Juvenile films; Rapunzel (Tale) -- Film and video adaptations; Children's films; Animated; Adventure; Barbie (Personnage fictif) -- Romans, nouvelles, etc. pour la jeunesse; Films anim?s.; DVD vid?o.; Films pour handicap?s auditifs; Barbie (Fictitious character); Fairy tales; Animated films; Feature films; Children's films; Video recordings for the hearing impaired; Fiction films; Adaptations; Films; Juvenile works